THE ROLE OF SOCIALIZATION INSTITUTIONS IN IMPARTING VIOLENT BEHAVIOR TO THE CHILD - Chabanne Mahdia (International Journal of Innovative Technologies in Social Science, 2025)
Childhood is a fundamental and critical stage of human development, marking the beginning of personality formation and growth. A child is born unable to perform any actions or comprehend their surroundings, requiring care through the establishment of rules that govern them. Through the processes of learning and education, adults transmit skills and values to children, equipping them with behaviors, norms, and attitudes suitable for specific social roles. This enables children to engage with the community and achieve social adjustment, facilitating their integration into social life. This process is part of socialization, which shapes the childs personality through an understanding of their behaviors. If socialization is healthy,it fosters a sound generation; conversely, if it is disrupted, it may lead to various deviant behaviors, such as substance abuse, theft, violence, and more. Thus, this research paper aims to uncover the role of socialization through its institutions—namely the family, school, peer groups, and media in the acquisition of violent behavior in children. The study concludes that eachsocialization institution plays a significant role in either mitigating orexacerbating violent behavior.